Theoretical analysis of the microwave radiation interaction with animals suffering by mastitis - Мазур, Виктор Анатольевич (Technology audit and production reserves, 2015)
To analyze the distribution of electric intensity of radio-pulse radiation in the mammary gland of ewes it is developed the model in the form of a truncated circular cone shape, filled with an isotropic medium with a different dielectric permittivity. In this article we solve the problem of homogeneous Maxwell equations describing distribution of the electric and magnetic fields in the module of the breast ewes by the method of integral equations. As a result of reforms, the initial transient problem has been reduced to the following series of problems of the diffraction of monochromatic fields with frequency for the area of the mammary gland of ewes. Formulated diffraction problems are reduced to integral equations for the field of the mammary gland of ewes. To this aim, using Green's formula, it was obtained integral equation for the distribution of the electric field inside mammary gland. A theoretical analysis found that for the treatment of infectious mastitis of ewes should be carried out using radio-pulse radiation with frequency 30,8 GHz, pulse width 1·10-6 sec, pulse repetition period 1·10-4 sec, radio pulse amplitude within the sheep udder (pulse, argon irradiation time of patients) for the treatment of mastitis of the ewes.